Profile and Analysis of Lightning Victims Brought to MGH, Khammam; Telangana State - Guntheti, Bharath Kumar; Singh , Uday Pal (Journal of Indian Academy of Forensic Medicine, 2015)
When there is discharge of electricity between clouds lightning occurs. This study was aimed to study the profile and analysis of lightning victims and pattern of injuries. Thirty Eight victims of lightning fatalities were identified from emergency Dept. of MGH, Dept. of Forensic Medicine, for a period of 3 years. Middle aged males, married, illiterates from rural region, belongs to low socioeconomic group, Hindu community are the most common victims when working as farmers in the open field afternoon time on Saturdays with peak incidence in monsoon season. The pattern of injuries is noted as burns over body in 36 (94.73%) cases with maximum cases having Lichtenberg figures 26 (68.42%), followed by linear burns 8 (21.05%). Magnetization of the metal worn noted. Maximum cases 34 (89.47%) were brought dead, post-mortem findings were nonspecific, petechial hemorrhage seen in the brain and the spinal cord. Cardiopulmonary arrest following lightning was most common in 28 (77.77%) cases. High incidence of lightning strikes in this region and requires a more systemic and detailed investigative protocol in lightning related deaths. Such deaths are unpredictable but preventable with better public education, rural health care.